TOWARD ADOPTION OF DRIP IRRIGATION AND SOIL-MOISTURE SENSORS BY SMALL-SCALE FARMERS - Ahmad, Lawal; Jafar Shanono, Nura; Mustapha Nasidi, Nuradeen (FUDMA JOURNAL OF SCIENCES, 2022)
The semi-arid region of the world is occasionally affected by erratic rainfall and drought which threatens agricultural production and food security. This paper presents the outcome obtained from a review to provide proactive measures that will combat the problems of water scarcity through the adoption of sensor-based drip irrigation by small-scale farmers. The small-scale farmers constituted the larger proportion of the farming population in the region. The paper is centred on the general overview of irrigation practices, advances in irrigation systems, modelling irrigation and cropping Systems, coupling soil sensors with drip irrigation and their adoption. Factors that hinder the acceptance and adoption of sensor-based drip irrigation systems were reviewed and synthesized which include initial capital investment, farmers’ awareness, risk perception and uncertainties, technical know-how, farm size and capital recovery. A simple framework for adopting a sensor-based drip irrigation system was developed. The building blocks of the framework include the dissemination of sensor-based irrigation to farmers, the creation of awareness among farming communities, and the provision of subsidies and credit. Others include the provision of policies and environmental standards and review of the price of water charges. This study will be useful to farmers, agricultural extension agents and policymakers in making decisions about the water resources planning and farming activities in the region.